Carbon fibers coated with graphene reinforced TiAl alloy composite with high strength and toughness - Sen Cui (Nature Portfolio, 2018)
Abstract To meet the more rigorous requirement in aerospace industry, recent studies on strengthening and toughening TiAl alloys mostly focus on high Nb addition, which inevitably bring in an increasing of density. In this study, a carbon fibers coated with graphene reinforced TiAl alloy composite was fabricated by powder metallurgy, melt spun and vacuum melting. This composite got remarkable mechanical properties combined with a prominent density reduction. In contrast with pure TiAl ingots, this sample exhibits an average fracture strain from 16% up to 26.27%, and an average strength from 1801 MPa up to 2312 MPa. Thus, we can achieve a new method to fabricate this low-density, good mechanical performance TiAl composite which could bring in more opportunities for application in aerospace industry.